DETERMINATION OF THE POPULATION DENSITY OF TIARIS CANORA (GMELIN, 1789) AND TIARIS OLIVACEUS (LINNAEUS, 1766) IN ZONE (3) OF THE PROTECTED AREA CUBANACÁN - ARMIÑANA-GARCÍA, Rafael (2023)
The research carried out consisted of determining the population density of Tiaris canora and Tiaris olivaceus in zone number three of the Cubanacán Protected Area, framed within the Cubanacán Heights in the province of Villa Clara, Cuba. For the capture of the birds, traps or rocker cages were used. The capture, marking and recapture of the birds under study constituted the basic method to determine the population density of the genus Tiaris. In addition, different methods were used to collect and process information, including interviews with 50 people in the city of Santa Clara, who illegally keep these species in captivity. From the study carried out in the sub-areas in zone three, the presence of 412.1 specimens of the genus Tiaris was confirmed, of which 207.9 were T. canora and 204.1 T. olivaceus, which confirmed that there is an index of abundance of this genus, taking into consideration the numerical relation of the species based on the area it occupies and that the number of specimens of the genus is equitable between the two species under study. In the capture processes, a greater number of males than females were obtained. It is concluded that research on this subject should be continued, but with other species of the Cuban avifauna, in order to know the distribution of the populations and to take the pertinent measures to continue protecting the biological diversity of Cuba.